Buro by Locaa Co.: The feasibility of fermented condiment business - Alo, Loren Sidney A.; Chua, Anne Kyla M.; De Leon, Chariz Joy C.; Osio, Ma. Olivia Francia C.; Pacardo, Aliah Jamaia 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2